Glycodelin-A stimulates the conversion of human peripheral blood CD16−CD56bright NK cell to a decidual NK cell-like phenotype. Issue 4 (28th December 2018) - Lee, Cheuk-Lun; Vijayan, Madhavi; Wang, Xia; Lam, Kevin K W; Koistinen, Hannu; Seppala, Markku; Li, Raymond H W; Ng, Ernest H Y; Yeung, William S B; Chiu, Philip C N
Abstract: STUDY QUESTION: Does glycodelin-A (GdA) induce conversion of human peripheral blood CD16 − CD56 bright natural killer (NK) cells to decidual NK (dNK) cells to facilitate placentation? SUMMARY ANSWER: GdA binds to blood CD16 − CD56 bright NK cells via its sialylated glycans and converts them to a dNK-like cells, which in turn regulate endothelial cell angiogenesis and trophoblast invasion via vascular endothelial growth factor (VEGF) and insulin-like growth factor-binding protein 1 (IGFBP-1) secretion, respectively. WHAT IS KNOWN ALREADY: dNK cells are the most abundant leucocyte population in the decidua. These cells express CD16 − CD56 bright phenotype. Peripheral blood CD16 − CD56 bright NK cells and hematopoietic precursors have been suggested to be capable of differentiating towards dNK cells upon exposure to the decidual microenvironment. These cells regulate trophoblast invasion during spiral arteries remodelling and mediate homoeostasis and functions of the endothelial cells. GdA is an abundant glycoprotein in the human decidua with peak expression between the 6th and 12th week of gestation, suggesting a role in early pregnancy. Indeed, GdA interacts with and modulates functions and differentiation of trophoblast and immune cells in the human feto-maternal interface. Aberrant GdA expression during pregnancy is associated with unexplained infertility, pregnancy loss and pre-eclampsia. STUDY DESIGN, SIZE, DURATION: CD16 + CD56 dim, CD16 − CD56 bright and dNK cells were isolated from human peripheral blood and decidua tissue, respectively, by immuno-magnetic beads or fluorescence-activated cell sorting. Human extravillous trophoblasts were isolated from first trimester placental tissue after termination of pregnancy. Biological activities of the cells were studied after treatment with GdA at a physiological dose of 5 μg/mL. GdA was purified from human amniotic fluid by immuno-affinity chromatography. PARTICIPANTS/MATERIALS, SETTING, METHODS: Expression of VEGF, CD9, CD49a, CD151 and CD158a in the cells were determined by flow cytometry. Angiogenic proteins in the spent media of NK cells were determined by cytokine array and ELISA. Blocking antibodies were used to study the functions of the identified angiogenic proteins. Endothelial cell angiogenesis was determined by tube formation and trans-well migration assays. Cell invasion and migration were determined by trans-well invasion/migration assay. Binding of normal and de-sialylated GdA, and expression of L-selectin and siglec-7 on the NK cells were analysed by flow cytometry. The association between GdA and L-selectin on NK cells was confirmed by immunoprecipitation. Extracellular signal-regulated protein kinases (ERK) activation was determined by Western blotting and functional assays. MAIN RESULTS AND THE ROLE OF CHANCE: GdA treatment enhanced the expression of dNK cell markers CD9 and CD49a and the production of the functional dNK secretory product VEGF in the peripheral blood CD16 − CD56 bright NK cells. The spent media of GdA-treated CD16 − CD56 bright NK cells promoted tube formation of human umbilical vein endothelial cells and invasiveness of trophoblasts. These stimulatory effects were mediated by the stimulatory activities of GdA on an ERK-activation dependent production of VEGF and IGFBP-1 by the NK cells. GdA had a stronger binding affinity to the CD16 − CD56 bright NK cells as compared to the CD16 + CD56 dim NK cells. This GdA-NK cell interaction was reduced by de-sialylation. GdA interacted with L-selectin, expressed only in the CD16 − CD56 bright NK cells, but not in the CD16 + CD56 dim NK cells. Anti-L-selectin functional blocking antibody suppressed the binding and biological activities of GdA on the NK cells. LARGE SCALE DATA: N/A. LIMITATIONS, REASONS FOR CAUTION: Some of the above findings are based on a small sample size of peripheral blood CD16 − CD56 bright NK cells. These results need to be confirmed with human primary dNK cells. WIDER IMPLICATIONS OF THE FINDINGS: This is the first study on the biological role of GdA on conversion of CD16 − CD56 bright NK cells to dNK-like cells. Further investigation on the glycosylation and functions of GdA will enhance our understanding on human placentation and placenta-associated complications with altered NK cell biology. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by the Hong Kong Research Grant Council Grant 17122415, Sanming Project of Medicine in Shenzhen, the Finnish Cancer Foundation, Sigrid Jusélius Foundation and the Finnish Society of Clinical Chemistry. The authors have no competing interests to declare.